Towards modelling tick-virus interactions using the weakly pathogenic Sindbis virus: Evidence that ticks are competent vectors - Wang, Yanan; Xu, Zhengmao; Zhang, Houshuang; Zhou, Yongzhi; Cao, Jie; Zhang, Yuqiang; Wang, Zedong; Zhou, Jinlin (Frontiers in Cellular and Infection Microbiology, 2024)
Most tick-borne viruses (TBVs) are highly pathogenic and require high biosecurity, which severely limits their study. We found that Sindbis virus (SINV), predominantly transmitted by mosquitoes, can replicate in ticks and be subsequently transmitted, with the potential to serve as a model for studying tick-virus interactions. We found that both larval and nymphal stages of Rhipicephalus haemaphysaloides can be infected with SINV-wild-type (WT) when feeding on infected mice. SINV replicated in two species of ticks (R. haemaphysaloides and Hyalomma asiaticum) after infecting them by microinjection. Injection of ticks with SINV expressing enhanced Green Fluorescent Protein (eGFP) revealed that SINV-eGFP specifically aggregated in the tick midguts for replication. During blood-feeding, SINV-eGFP migrated from the midguts to the salivary glands and was transmitted to a new host. SINV infection caused changes in expression levels of tick genes related to immune responses, substance transport and metabolism, cell growth and death. SINV mainly induced autophagy during the early stage of infection; with increasing time of infection, the level of autophagy decreased, while the level of apoptosis increased. During the early stages of infection, the transcript levels of immune-related genes were significantly upregulated, and then decreased. In addition, SINV induced changes in the transcription levels of some functional genes that play important roles in the interactions between ticks and tick-borne pathogens. These results confirm that the SINV-based transmission model between ticks, viruses, and mammals can be widely used to unravel the interactions between ticks and viruses.